Amino acid mediated synthesis of silver nanoparticles and preparation of antimicrobial agar/silver nanoparticles composite films. (5th October 2015) - Shankar, Shiv; Rhim, Jong-Whan
Highlights: AgNPs were synthesized using amino acids as reducing and capping agents. Agar/AgNPs nanocomposite films were prepared by solvent casting method. Nanocomposite films exhibited a UV screening effect without sacrificing the mechanical and WVP properties. All agar/AgNPs composite films showed strong antimicrobial activity against E. coli and L. monocytogenes . Abstract: Silver nanoparticles (AgNPs) were synthesized using amino acids (tyrosine and tryptophan) as reducing and capping agents, and they were incorporated into the agar to prepare antimicrobial composite films. The AgNPs solutions exhibited characteristic absorption peak at 420 nm that showed a red shift to ∼434 nm after forming composite with agar. XRD data demonstrated the crystalline structure of AgNPs with dominant (1 1 1) facet. Apparent surface color and transmittance of agar films were greatly influenced by the AgNPs. The incorporation of AgNPs into agar did not exhibit any change in chemical structure, thermal stability, moisture content, and water vapor permeability. The water contact angle, tensile strength, and modulus decreased slightly, but elongation at break increased after AgNPs incorporation. The agar/AgNPs nanocomposite films possessed strong antibacterial activity against Listeria monocytogenes and Escherichia coli . The agar/AgNPs film could be applied to the active food packaging by controlling the food-borne pathogens.